2015
DOI: 10.3389/fnins.2015.00340
|View full text |Cite
|
Sign up to set email alerts
|

Golgi fragmentation in Alzheimer's disease

Abstract: The Golgi apparatus is an essential cellular organelle for post-translational modifications, sorting, and trafficking of membrane and secretory proteins. Proper functionality of the Golgi requires the formation of its unique cisternal-stacking morphology. The Golgi structure is disrupted in a variety of neurodegenerative diseases, suggesting a common mechanism and contribution of Golgi defects in neurodegenerative disorders. A recent study on Alzheimer's disease (AD) revealed that phosphorylation of the Golgi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 106 publications
(135 reference statements)
2
90
0
Order By: Relevance
“…Indeed, trafficking and maturation of APP, its processing enzymes and Aβ production have been shown to be dependent on the integrity of the GA (Burgos et al, 2010, Choy et al, 2012, Greenfield et al, 1999, Huse et al, 2002, Joshi et al, 2015, Joshi and Wang, 2015). In addition, in the APPswe/PS1ΔE9 animal model of AD, it has been reported that the accumulation Aβ peptide in neurons might induce GA fragmentation, thereby accelerating the traffic of APP and the production of Aβ (Joshi et al, 2015, Joshi and Wang, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, trafficking and maturation of APP, its processing enzymes and Aβ production have been shown to be dependent on the integrity of the GA (Burgos et al, 2010, Choy et al, 2012, Greenfield et al, 1999, Huse et al, 2002, Joshi et al, 2015, Joshi and Wang, 2015). In addition, in the APPswe/PS1ΔE9 animal model of AD, it has been reported that the accumulation Aβ peptide in neurons might induce GA fragmentation, thereby accelerating the traffic of APP and the production of Aβ (Joshi et al, 2015, Joshi and Wang, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Proper functioning of the GA is necessary for Aβ production and for trafficking and maturation of amyloid precursor protein APP and its processing enzymes (Burgos et al, 2010, Choy et al, 2012, Greenfield et al, 1999, Huse et al, 2002, Joshi et al, 2015). In addition, studies using the APPswe/PS1ΔE9 animal model of the disease have reported that the accumulation of Aβ peptides leads to Golgi fragmentation, mediated by cdk5-dependent phosphorylation of Grasp 65, which in turn accelerates APP trafficking and Aβ production (Joshi et al, 2015, Joshi and Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is relevant to human disorders where the Golgi structure is fragmented. In Alzheimer’s disease, Golgi fragmentation resulted from GRASP65 phosphorylation by activated Cdk5 accelerated the trafficking of the amyloid precursor protein (APP) and thus increases amyloid beta (Aβ) production, which could be reversed by expressing non-phosphorylatable GRASP proteins [7880]. …”
Section: Golgi Structure Formation and Protein Glycosylationmentioning
confidence: 99%
“…A typical morphological anomaly of the Golgi apparatus is fragmentation, which is observed in Golgi-associated protein deletion mutants, stress-exposed cells, and diseases (5)(6)(7)(8)(9)(10). Via the fragmentation, Golgi components completely decompose and lose their morphological characteristics such as the structural anisotropy and long-range coherence.…”
mentioning
confidence: 99%